STUDI KASUS PENETAPAN KEMBALI TARIF DAN/ATAU NILAI PABEAN (SPKTNP) OLEH DIREKTUR JENDERAL BEA DAN CUKAI: TINJAUAN PUTUSAN PENINJAUAN KEMBALI MAHKAMAH AGUNG RI - Firdiansyah, Akhmad; Hasyim, Wachid; Pahlevi, Yonathan Agung (Politeknik Keuangan Negara STAN)
ABSTRACTÂ In accordance with the mandate of Article 23A of the 1945 Constitution, all tax stipulations must be based on the law. To carry out the mandate in accordance with Article 17 of the Customs Law Number 17 of 2006, the Director General of Customs and Excise is given the attributive authority to issue reassignment letter on Customs Tariff and / or Value for the calculation of import duty within two years starting from the date of customs notification carried out through a mechanism of audit or re-research. To examine the application of these legal norms, there are currently Supreme Court (MA) Judgment (PK) decisions that accept PK applications from PK applicants and question the legality of issuing SPKTNP by the Director General of BC. This study uses explosive qualitative analysis to analyze the issuance of SPKTNP by the Director General of BC. The results of this study indicate that the Supreme Court is of the view that the issuance of SPKTNP by the Director General of BC is a legal defect, while DGCE considers the issuance of SPKTNP by the Director General of BC according to the provisions.Key words: official decision, reassignment letter, DCGEÂ Â ABSTRAKSesuai amanah Pasal 23A Undang-Undang Dasar 1945 Segala penetapan pajak harus berdasar undang-undang. Untuk menjalankan amanah tersebut sesuai Pasal 17 Undang-Undang Kepabeanan Nomor 17 Tahun 2006 Direktur Jenderal Bea dan Cukai (Dirjen BC) diberikan kewenangan atributif untuk menerbitkan Surat Penetapan Kembali Tarif dan/atau Nilai Pabean (SPKTNP) guna penghitungan bea masuk dalam jangka waktu dua tahun terhitung sejak tanggal pemberitahuan pabean yang dilakukan melalui mekanisme audit atau penelitian ulang. Untuk meneliti penerapan norma hukum tersebut dewasa ini terdapat putusan Peninjauan Kembali (PK) Mahkamah Agung (MA) yang menerima permohonan PK dari pemohon PK dan mempermasalahkan legalitas penerbitan SPKTNP oleh Dirjen BC. Penelitian ini mengunakan analisis kualitatif eksplotarif untuk menganalisis penerbitan SPKTNP oleh Dirjen BC. Hasil penelitian ini menunjukkan bahwa MA berpandangan penerbitan SPKTNP oleh Dirjen BC adalah cacat hukum, sedangkan DJBC beranggapan penerbitan SPKTNP oleh Dirjen BC telah sesuai ketentuan.Kata Kunci: penetapan pejabat, SPKTNP, Direktur Jenderal Bea dan Cukai.